Integrated use of herbicide and straw mulch in suppressing the weed species in summer sesame (Sesamum indicum) - FATIMA, AYESHA; DUARY, B (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted during the summer (pre-kharif) season of 2016 at the Agricultural Farm of the Institute of Agriculture (Palli Siksha Bhavana), Visva-Bharati, Sriniketan, Birbhum, West Bengal. The experiment comprising two factors; three cultivars and five weed management practices was laid out in a factorial randomized block design with three replications. Digitaria sanguinalis, among the grasses; Cyperus rotundus, among the sedges and Spilanthes acmella, among the broadleaved weeds were predominant throughout the cropping period of sesame (Sesamum indicum L.). The cultivar Rama recorded significantly the lower values of weed density, dry weight; higher values of capsules per plant (40), seeds per capsule(53) and seed yield (1181 kg ha-1) of sesame. Among the weed control treatments, integrated use of pendimethalin at 1.0 kg ha-1 at 1 PE + straw mulching at 3.5 t ha-1 at 15 DAS registered the lower weed density as well as dry weight of grassy, broadleaved, sedge and total weeds at 45 and 60 DAS; higher number of capsules plant-1 (41), seeds capsule-1(49), seed yield (1123 kg ha-1) and higher weed control efficiency (94.36%) at 60 DAS. The cultivar Rama with pendimethalin at 1.0 kg ha-1at PE + straw mulching at 3.5 t ha-1 was found to be effective in controlling composite weed flora. Lower values of weed density and weed dry weight; higher values of yield and yield attributes of sesame and weed control efficiency were registered with combination of cultivar Rama and pendimethalin at 1.0 kg ha-1 at PE + straw mulching at 3.5 t ha-1 at 15 DAS. The treatment straw mulching at 3.5 t ha-1 was found to be effective in controlling broadleaved weeds. Thus, integrated use of weed competitive cultivar Rama along with pendimethalin at 1.0 kg ha-1 at PE + straw mulching at 3.5 t ha-1 at 15 DAS appeared to be the most promising approach for effective weed management and obtaining higher productivity of summer sesame.